New species of Fannia Robineau-Desvoidy (Diptera: Fanniidae) from Colombia - Durango, Yesica; Ramírez-Mora, Manuel (Zootaxa, 2013)
Fannia Robineau-Desvoidy is a genus of calyptrate Diptera that comprises 89 Neotropical species, of which only 23 occur in Colombia. Based on male characters (including terminalia), two new species from the Department of Antioquia (Fannia colazorrensis sp. nov. and Fannia laclara sp. nov.) are described. Illustrations of the male are presented.